Phenomena of bullying behaviour on adolescents in boarding school - Ema Waliyanti; Fauziah Anggitha Swesty (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: A large number of bullying cases occurred on adolescents in boarding schools can impact on physical and psychological conditions that make them inconvenient in their schools and boarding schools. Boarding schools are more prone of bullying incidents than public schools because their students interact each other more often, either in their schools or dorms. Objective: This study aims to observe bullying behaviour of adolescents in a boarding school in Yogyakarta.Methods: This study was a qualitative method with a phenomenological approach. Its data collection technique was conducted by interviewing. There were 11 participants in this study consisting of eight adolescents and three boarding school teachers who were determined by a purposive sampling. To validating its data, this study used a source triangulation, peer debriefing, and thick description. Then, its data analysis applied the Open Code 4.03. Results: This study showed that bullying behaviour occurred in the boarding school were physical bullying, verbal bullying and relational bullying. Factors that contributed for the bullying behaviour were physical forms, social intercourses of adolescent, emotional attitudes, histories of bullying, seniority, and bullying punishment that are applied ineffectively. Responding to the bullying incidents, the boarding school made policies by making rules about bullying, intervening by advice, applying school punishment, and initiating preventative effortsConclusion: Bullying behaviour of the adolescent occurred in the boarding school includes physical bullying, verbal bullying, and relational bullying that requires attention from all parties, including schools. Schools are expected to provide socialization related to the bullying and to cooperate with all school members to prevent repetitive incidents of bullying.